Analysis of the Influence of Franchises and Pricing Strategies on Business Development in Malaysia - Abdullah , Abdullah (PERFECT EDUCATION FAIRY, 2024)
This study aims to analyze the influence of franchise ownership and pricing strategies on business development in Malaysia. The franchise business model is increasingly popular in the retail and service sector because it offers advantages in the form of brand recognition, operational standards, and managerial support that can accelerate business growth. Meanwhile, pricing strategies are a crucial marketing instrument to increase competitiveness and consumer loyalty. This study uses a quantitative approach with simulation data of 200 observations and analyzed using multiple linear regression through  the Ordinary Least Squares (OLS) method. The dependent variable is business development (BusinessDev), while the independent variable consists of Franchise and PriceStrategy. The results of the study show that both independent variables have a positive and significant effect on business development. Franchise ownership increased the business development score by 1.61 points, while pricing strategies had an effect of 0.88 points. This model is able to explain 43.3% of the variation in business development. These findings confirm that the combination of franchises and the right pricing strategy has the potential to increase the competitiveness of businesses in Malaysia. This research contributes to the development of the business management literature and provides practical recommendations for business actors and policymakers in strengthening the entrepreneurial ecosystem in the Southeast Asian region.